Total knee arthroplasty associated with tibial tubercle and simultaneous femoral and tibial osteotomies for severe extra-articular deformity: a case report - Sponer P; Kucera T (Dove Medical Press, 2019)
Pavel Sponer, Tomas KuceraDepartment of Orthopedic Surgery, Charles University, Faculty of Medicine in Hradec Kralove, Hradec Kralove, 500 38, Czech RepublicAbstract: The restoration of the lower extremity mechanical axis in patients with osteoarthritis in knee and extra-articular deformity requires careful pre-operative planning. An extra-articular deformity may be corrected inside the knee by arthroplasty with intra-articular correction or outside of the knee by osteotomy alone or by arthroplasty combined with extra-articular corrective osteotomy. In this study, we described a unique case of simultaneous femoral and tibial osteotomies at the time of primary total knee arthroplasty in a 45-year-old woman. To prevent unnecessary bone loss, the intra-articular bone resections were made parallelly to the preexisting joint obliquity prior to the corrective tibial and femoral osteotomies. After restoration of the mechanical axis and healing of all osteotomies, a successful clinical and radiological outcome was achieved during the mid-term 5-year follow-up. The preoperative analysis of patients with an extra-articular deformity is invaluable and should include long-standing radiographs from the center of the femoral head to the center of the ankle. Although different osteotomy principles (opening wedge vs closing wedge) and fixation methods (stemmed revision prosthesis, intramedullary nail, locking plates) have been reported in the literature, the use of a tapered fluted long stem offers several benefits, including ease of application, rotational control, and possible early weight bearing. Total knee arthroplasty in combination with simultaneous extra-articular osteotomy is technically difficult but effective. This technique helps to preserve bone stock and ligament stability. A single intervention leads to less recovery time, reduced risk to the patients by avoiding two separate applications of anesthesia, and reduced costs. Based on the literature search, this is the first report describing the detailed surgical technique of simultaneous femoral and tibial osteotomies at the time of primary total knee arthroplasty associated with tibial tubercle osteotomy, achieving a comprehensive correction.Keywords: osteoarthritis, extra-articular deformity, total knee arthroplasty, femoral osteotomy, tibial osteotomy